2018
DOI: 10.3389/feart.2018.00167
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics and Distribution of Trace Elements in Precious Corals

Abstract: The concentration and spatial distribution of major (Ca, Mg) and trace elements (Na, Sr, S, Li, Ba, Pb, and U) in different Corallium skeletons (C. rubrum, C. japonicum, C. elatius, C. konojoi) have been studied by electron microprobe (EMP) and laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS). EMP data show positive Na-Mg and negative Na-S and Mg-S correlations in all skeletons. LA-ICPMS data display additional Sr-Mg, Li-Mg, and U-Mg positive correlations. Medullar zones in the skeletons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 75 publications
6
39
0
Order By: Relevance
“…The Sciacca samples dated ~2100-2400 BP and ~4050-4400 BP represent times before the widespread introduction of Pb into the environment through human activities. Interestingly, the mean concentrations measured on present-day corals in this dataset are remarkably consistent with those determined by Vielzeuf et al (2018), except for K and Zn that show slight differences. In the VT dataset, compared to present-day corals, the sub-fossil samples are enriched in Mn (48 ± 17 vs 0.9 ± 0.5 µg/g), Fe (172 ± 107 vs 0.69 ± 0.04 µg/g), Cu (1.6 ± 1.6 vs 0.15 ± 0.02 µg/g), and U (0.26 ± 0.15 vs 0.08 ± 0.04 µg/g).…”
Section: Lead Contents In Sub-fossil C Rubrum Skeletons From the Medsupporting
confidence: 85%
See 3 more Smart Citations
“…The Sciacca samples dated ~2100-2400 BP and ~4050-4400 BP represent times before the widespread introduction of Pb into the environment through human activities. Interestingly, the mean concentrations measured on present-day corals in this dataset are remarkably consistent with those determined by Vielzeuf et al (2018), except for K and Zn that show slight differences. In the VT dataset, compared to present-day corals, the sub-fossil samples are enriched in Mn (48 ± 17 vs 0.9 ± 0.5 µg/g), Fe (172 ± 107 vs 0.69 ± 0.04 µg/g), Cu (1.6 ± 1.6 vs 0.15 ± 0.02 µg/g), and U (0.26 ± 0.15 vs 0.08 ± 0.04 µg/g).…”
Section: Lead Contents In Sub-fossil C Rubrum Skeletons From the Medsupporting
confidence: 85%
“…Conversely, it was shown that growth kinetics does not influence the incorporation of Ba and Pb. Concerning lead, large variations of concentrations in corals were observed (Vielzeuf et al, 2018). These data raised the question of the origin and significance of the variations of lead in Corallium skeletons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We cannot resolve with our data set the causes for these multi elemental cycles, but it should be mentioned that such cycles are also observed in other biomineralizing systems: clams (e.g,. Warter et al, 2018), corals (e.g., Vielzeuf et al, 2018) and others. Our observation that DIC did not affect the pattern of elemental cycles within the shells suggest that these variations are indeed an essential part of the calcification process that may be strongly biologically controlled and therefore are not influenced by the DIC.…”
Section: The Effect Of Dic On Intra-shell Variabilitymentioning
confidence: 99%